A neglected ocular tuberculosis without antitubercular therapy: A case report - Oktaliani, Rahayu; Idrus, Elfa Ali (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Ocular tuberculosis (TB) is one of the causes of uveitis, but there is often a skepticism and lack of acceptance regarding this diagnosis. We present a case of a-62-year-old female patient who complained of blurred vision, pain, and redness in her right eye. These symptoms had persisted for the past 16 months. The latest visual acuity in the right eye was 0.0167, and in the left eye was 0.63. Upon examination, keratic precipitates were found in the right eye, along with flare and cells +1/+1, pupil seclusion, a cloudy lens, and opacity in the posterior segment. The left eye was within normal limits. The patient was diagnosed with panuveitis of the right eye due to ocular TB and a complicated cataract. She had been referred by the local general hospital with complaints of blurred vision and was initially diagnosed with anterior uveitis due to ocular TB based on clinical presentation and positive Interferon-Gamma Release Assay (IGRA) test results. The patient was then referred back to the Internal Medicine Department of the local general hospital and the community health centre to start the anti-tuberculosis therapy (ATT). However, the patient refused treatment and, as a result, did not receive anti-tuberculosis drugs. Panuveitis TB, without adequate treatment, can lead to a poor prognosis.